Penyerahan Sukarela Jaminan Fidusia dalam Perspektif Hukum dan Keadilan - Probo Pribadi S.M (Perkumpulan Maju Karya Yogyakarta, 2026)
Voluntary surrender of fiduciary guarantee is a debt settlement mechanism that allows debtors to surrender collateral objects to creditors without formal execution proceedings. This article examines such practice from legal and justice perspectives to identify gaps between regulation and implementation. Using normative juridical method with doctrinal and comparative analysis, this study traces the legal basis of voluntary surrender under Law Number 42 of 1999 on Fiduciary Guarantee, Constitutional Court decisions, and civil law principles. The analysis reveals that although voluntary surrender is formally valid, its practice often creates injustice due to information asymmetry, concealed pressure, and weak debtor protection. Constitutional Court Decisions Number 18/PUU-XVII/2019 and Number 2/PUU-XIX/2021 have provided constitutional influence on debtor protection, yet implementation requires strengthened oversight and dispute resolution mechanisms. This article recommends regulatory updates, enhanced legal literacy, and establishment of accompaniment institutions to ensure balance between legal certainty for creditors and protection of debtor rights.